Effects of Vitamin D-Deficient Diet on Intestinal Epithelial Integrity and Zonulin Expression in a C57BL/6 Mouse Model - Yeung, Chun-Yan; Chiang Chiau, Jen-Shiu; Cheng, Mei-Lein; Chan, Wai-Tao; Jiang, Chuen-Bin; Chang, Szu-Wen; Liu, Chia-Yuan; Chang, Ching-Wei; Lee, Hung-Chang (Frontiers in Medicine, 2021)
Background and aims Vitamin D (VD) plays important role not only in mineral balance and skeletal maintenance but also in immune modulation. VD status was found correlated with the pathophysiology and severity of inflammatory bowel diseases and other autoimmune disorders. Epithelial barrier function is primarily regulated by the tight junction (TJ) proteins. In this study, we try to establish an animal model by raising mice fed VD deficient diet and to investigate the effects of VD deficient diet on gut integrity and zonulin expression. Methods: Male C57BL/6 mice were administered either VD deficient (VDD group, 25(OH)2D3 0 IU/per mouse) or VD sufficient (VDS group, 25(OH)2D3 37.8 IU/per mouse) special diets for 7 weeks. Serum VD levels were detected. After sacrificed, jejunum and colon specimens were collected. Villus length and crypt depth of jejunum as well as colon mucosa thickness were measured. Various serum pro-inflammatory cytokines and intestinal TJ proteins were assessed. Serum level of zonulin and mRNA expression of jejunum zonulin were also investigated. Results: We found mice fed VDD diet had a lower serum level of VD after 7 weeks (p<0.001). VDD mice gained significant less weight (p=0.017) and took similar amount of diet (p=0.398) when compared to mice raised on VDS diet. Significantly decreased colon mucosa thickness was found in VDD mice compared with VDS group (P=0.022). Marked increase in serum pro-inflammatory cytokine levels was demonstrated in VDD mice. All relative levels of CLD-1, CLD-3, CLD-7 and zonulin-1 protein expressions were significantly decreased in the VDD group. Significant up-regulation of mRNA expression of jejunum zonulin (p=0.043) and elevated serum zonulin (p=0.001) were found in VDD group. Conclusions: We demonstrated that VDD could lead to impaired barrier properties. We assume that sufficient VD could maintain intestinal epithelial integrity and prevent barrier dysfunction. VD may serve as part of therapeutic strategy for human autoimmune and infectious diseases with intestinal barrier dysfunction (leaky gut) in the future. To our knowledge, this is the first study to demonstrate VDD could lead to significant up-regulation in mRNA expression of jejunum zonulin level and a marked elevation of serum zonulin in a mouse model.